1959
DOI: 10.1042/bj0720654
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of amino acids into the cell-wall mucopeptide of staphylococci and the effect of antibiotics on the process

Abstract: I959 glucosamine and muramic acid; (b) a mucopeptide containing glyeine, muramic acid and glucosamrine; (c) a mueopeptide containing muranie acid, glyoine, lysine, glutamate and slanine. 4. All the fragments isolated are resistant to the action of lysozyme. 5. The significance of the mueopeptide fragments for the structure of the wall mucopeptide is discussed. We have much pleasure in acknowledging the technical assistance of Ian Mathison and Martyn Hodgson during the course of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

1962
1962
1972
1972

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(67 citation statements)
references
References 26 publications
2
64
0
1
Order By: Relevance
“…Park (1952) showed that penicillin caused accumulation of uridine-linked peptides which are believed to be precursors of cell-wall mucopeptide (Park & Strominger, 1957). Inhibition of mucopeptide synthesis by penicillin in washed staphylococci has been shown by Park (1958), Mandelstam & Rogers (1959) and Rogers & Jeljaszewicz (1961).…”
Section: Acid (Ampicillin)mentioning
confidence: 84%
See 3 more Smart Citations
“…Park (1952) showed that penicillin caused accumulation of uridine-linked peptides which are believed to be precursors of cell-wall mucopeptide (Park & Strominger, 1957). Inhibition of mucopeptide synthesis by penicillin in washed staphylococci has been shown by Park (1958), Mandelstam & Rogers (1959) and Rogers & Jeljaszewicz (1961).…”
Section: Acid (Ampicillin)mentioning
confidence: 84%
“…There are, however, some noteworthy differences between the two types of mucopeptide. In none of the Gram-negative strains examined did the mucopeptide amount to more than about 1 % of the bacterial mass, whereas in Gram-positive organisms the mucopeptide is usually 10-20 % [see, for example, Mandelstam & Rogers (1959)]. Apart from being a minor constituent of the cell, the Gram-negative mucopeptide is also a small part of the wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several effects, such as inhibition of induced enzyme synthesis and stimulation of efflux of K+ ions, could be ascribed to alterations in cell-membrane function. The antibiotic also inhibits incorporation of ['4C]aminoacids into cell walls and induces the accumulation of uridine-nucleotide precursors of the wall under conditions in which incorporation of amino acids into protein is unaffected (12)(13)(14)(15). However, since bacitracin affects protoplasts of bacteria, its action is not limited to effects on cell walls.…”
mentioning
confidence: 99%